Occurrence of Point Mutations in gyrA and parC Genes of Ciprofloxacin-Resistant Pseudomonas aeruginosa Isolated from Burn Infections - Abdulameer, Hajer H.; Abdulhassan, Ghusoon A. (Iraqi Journal of Science, 2021)
The spread of antibiotic resistant bacteria is a worldwide problem. Due to the importance of P. aeruginosa as a multidrug resistant bacterium, this study aimed, through molecular techniques, to detect point mutations in chromosomal genes responsible for the quinolones class of antibiotics resistance. A total of 52 isolates from burn infections were identified using specific primers for P. aeruginosa 16S rDNA. Ciprofloxacin minimum inhibitory concentrations (MIC) were estimated using the agar dilution assay. DNA sequences of the quinolone resistance-determining regions of gyrA and parC were determined for detecting the mutations found in these genes and the relations among the isolates by constructing phylogenetic trees. The results revealed that only 43 (82.7%) of isolates were P. aeruginosa, of which 31 (72.06%) were resistant to different concentrations of ciprofloxacin, ranging between 4 and >32 µg/ml. Twenty six isolates were selected for sequencing, including sensitive, intermediately resistant, and highly resistant to ciprofloxacin. The ciprofloxacin sensitive isolates did not exert any amino acid alterations in gyrA or parC genes; however, a single intermediately resistant isolate had a single mutation at each gene. Of the total resistant isolates (20), 6 isolates had no mutations at different MIC levels, While 14 isolates had Thr-83-Ile substitution in gyrA and Ser-87-Leu substitution in parC, only five isolates had a second mutation, namely Asp-87-Asn, in gyrA. The phylogenetic analysis of the studied groups showed divergence from the P. aeruginosa PAO1 and PAO1OR reference strains due to increased mutations and polymorphisms in studied isolates. In conclusion, P. aeruginosa occurrence was increased in burn infections and the fluoroquinolones in current use are not as effective as before; the main resistance mechanism in local clinical isolates of P. aeruginosa is mutations, where the main target of fluoroquinolones is gyrA gene.